Uncovering Arabia: A scenic design of Mary Zimmerman's The Arabian Nights. - Gottlieb, Jeffrey B. (Tufts Archival Research Center, 2005)
A reflection on the scenic design process for the Spring 2011 Departmental Production of Mary Zimmerman's The Arabian Nights, directed by Luke Jorgenson.